Information technologies in the system of higher education - Murzina, O. A.; Makyeyeva, L. V.; Pototska, O.; Sysoiev, O.; Kablukov, A.; Мурзіна, Олена Анатоліївна; Макєєва, Людмила Валеріївна; Потоцька, Олена Іванівна; Каблуков, Андрій Олександрович (My University, 2021)
The article discusses the need for widespread introduction of a component based on modern information technologies into distance learning. A brief analysis of the existing main educational initiatives of leading companies in distance e-learning is presented. Variants of a conscious choice of educational services and specific steps for their implementation in the educational process are proposed. It is emphasized that the use of these technologies in the educational process will improve the quality of training students in higher educational institutions, as well as reduce material costs for their education.
Keywords: distance learning; information technology; information resources platform; learning environment software